GLUCOCORTICOID-INDUCED OSTEOPOROSIS: DIAGNOSIS, PREVENTION, AND TREATMENT - N. V. Toroptsova (Научно-практическая ревматология)
The lecture gives information on the epidemiology and pathogenesis of glucocorticoid-induced osteoporosis (GCOP). It presents the latest diagnostic criteria, a modified FRAX algorithm (assessment of 10-year osteoporotic fracture risk) in relation to the taken dose of glucocorticoids, the data of recent clinical guidelines for the treatment and prevention of GCOP, and the specific features in relation to patient age.